От знаков к знаниям: образы и сюжеты обретения исторической субъектности в нарративах Олжаса Сулейменова - Krupko, I. V. (Journal of history, 2023)
The article is devoted to the study of some signs and images of world culture in the work of the poet, researcher and public figure of the XX-XXI centuries. Olzhas Suleimenov. The article studies the intellectual genealogy of the poet's use of the images of the Sumerian, Egyptian and ancient cultures in a dialogue with the autochthonous systems of knowledge and signs of the Kazakh and Turkic culture. In the article, we have studied the intellectual tradition created by Olzhas Suleimenov in the XXth century: in his poetic and scientific works, he reconstructs ancient signs, plots and archetypes of both Turkic and world cultures, comparing and exploring their common origin, as well as the history of their dialogue in antiquity and the Middle Ages. The studied literary and historiosophical material makes it possible to comprehend the problem of the correlation of nomadic and settled in the historical memory of Kazakhstani society and the presence of a cultural trauma of “non-historicality” here, overcome in the second half of the 20th century. The factors that shaped this cultural trauma include: 1) the interruption of nomadic culture as a result of forced collectivization and the transfer of nomads to settled life in the 1920s–1930s; 2) sedentarist narratives of describing nomadic culture as regressive and their overcoming by the Kazakh national intelligentsia of the 1960s–1970s. (represented by Olzhas Suleimenov) through the dominant historical narrative. The way to overcome this trauma was the dialogical assimilation of the cultural heritage of the medieval urban culture of Central Asia, the active archaeological research of which begins in these years in the Kazakh SSR, and the inscription of the reformatted historical subjectivity in the world history of civilization.